A guide to critiquing a research paper on clinical supervision: enhancing skills for practice. Issue 9 (13th May 2014) - Fothergill, A.; Lipp, A.
<x xml:space="preserve">Abstract</x> Accessible summary This paper aims to do two things: First, we want to show the reader how to critique a published research paper. The second aim is to take the reader through the various stages of critiquing using a guide. In the paper, we explain at each stage the research terms that can deter the novice critic from reading and understanding the findings in research. From this we hope the reader will have developed an ability to do their own critiquing, so that they are better informed about the quality of research that influences nursing practice. Abstract In this paper we have taken a previously published paper on the effectiveness of clinical supervision and undertaken a systematic critique of the merits of this quantitative research using a recognized critiquing framework compiled by Coughlan et al. (2007). Our purpose was twofold: First, we wanted to demonstrate the various stages of critiquing a paper in order that the reader might make an informed judgment of the quality and relevance of the research. The reader/critic is then able to decide whether to use this research in their own practice. Second, we wanted to assist the reader to develop their own critical, analytical skills through methodically appraising the merits of published research. Nursing as an evidence‐based profession requires nurses at both pre‐ and post‐registration level to be able to understand, synthesize and critique research, this being a fundamental part of many nursing curricula. These have become core skills to acquire because implementing up‐to‐date evidence is the cornerstone of contemporary nursing practice. We have provided in this paper a template for critiquing, which is based on our combined experiences as academics specifically in teaching at the bachelor, master's and doctoral levels.